Postconditioning effects of argon or xenon on early graft function in a porcine model of kidney autotransplantation. Issue 8 (30th March 2018) - De Deken, J.; Rex, S.; Lerut, E.; Martinet, W.; Monbaliu, D.; Pirenne, J.; Jochmans, I.
Abstract : Background: Ischaemia–reperfusion injury is inevitable during renal transplantation and can lead to delayed graft function and primary non‐function. Preconditioning, reconditioning and postconditioning with argon and xenon protects against renal ischaemia–reperfusion injury in rodent models. The hypothesis that postconditioning with argon or xenon inhalation would improve graft function in a porcine renal autotransplant model was tested. Methods: Pigs ( n  = 6 per group) underwent left nephrectomy after 60 min of warm ischaemia (renal artery and vein clamping). The procured kidney was autotransplanted in a separate procedure after 18 h of cold storage, immediately after a right nephrectomy. Upon reperfusion, pigs were randomized to inhalation of control gas (70 per cent nitrogen and 30 per cent oxygen), argon (70 per cent and 30 per cent oxygen) or xenon (70 per cent and 30 per cent oxygen) for 2 h. The primary outcome parameter was peak plasma creatinine; secondary outcome parameters included further markers of graft function (creatinine course, urine output), graft injury (aspartate aminotransferase, heart‐type fatty acid‐binding protein, histology), apoptosis and autophagy (western blot, terminal deoxynucleotidyl transferase dUTP nick‐end labelling (TUNEL) staining), inflammatory mediators and markers of cell survival/growth (mRNA and tissue protein quantification), and animal survival. Results are presented as median (i.q.r.). ANOVA and Kruskal–Wallis tests were used where indicated. Results: Peak plasma creatinine levels were similar between the groups: control 20·8 (16·4–23·1) mg/dl, argon 21·4 (17·1–24·9) mg/dl and xenon 19·4 (17·5–21·0) mg/dl ( P  = 0·607). Xenon was associated with an increase in autophagy and proapoptotic markers. Creatinine course, urine output, injury markers, histology, survival and inflammatory mediators were not affected by the intervention. Conclusion: Postconditioning with argon or xenon did not improve kidney graft function in this experimental model. Surgical relevance Ischaemia–reperfusion injury is inevitable during renal transplantation and can lead to delayed graft function and primary non‐function. Based on mainly small animal experiments, noble gases (argon and xenon) have been proposed to minimize this ischaemia–reperfusion injury and improve outcomes after transplantation. The hypothesis that postconditioning with argon or xenon inhalation would improve graft function was tested in a porcine kidney autotransplantation model. The peak plasma creatinine concentration was similar in the control, argon and xenon groups. No other secondary outcome parameters, including animal survival, were affected by the intervention. Xenon was associated with an increase in autophagy and proapoptotic markers. Despite promising results in small animal models, postconditioning with argon or xenon in a translational model of kidney autotransplantation was not beneficial. Clinical trials would require better results. Abstract : No for noble gases